(untitled) (Asian Journal of Plant Biology, 2022)
Some of agricultural pesticides contained polyacrylamide as a dispersant and wetting agent. Polyacrylamide is slowly degraded to acrylamide, a suspected carcinogen and a neurotoxicant that has been documented to cause deaths of ruminants exposed to this compound. An acrylamide-degrading bacterium has been isolated from polluted soils in Egypt. The bacterium was identified partially as Staphylococcus sp. strain Amr-15 based on biochemical tests. At room temperature, the effect of the initial pH on bacterial growth shows that the optimum pH range was discovered to be between 7.0 and 7.5. The optimal growing temperature at pH 7.5 ranged from 25 to 40 degrees Celsius. In a series of experiments using a 1.0 percent (w/v) starting concentration of various organic carbon sources, it was determined that both glucose and sucrose supported the greatest amount of cellular growth on acrylamide. Acrylamide dosages of up to 2000 mg/L were explored as a single nitrogen supply. The greatest growth occurred between 300 and 1000 mg/L of acrylamide, resulting in a nearly 7.0 log CFU/mL increase with a nett growth of near 3 log CFU/mL when compared to the control. Growth was practically tolerated at the highest dosage tested, 2000 mg/L, and growth stopped entirely at 2500 mg/L. Mercury at 2 ppm caused 82% of inhibition whilst other metal ions such as copper, cadmium, lead and chromium show from 30 to 50% inhibition. The concentration of acrylamide and the time it took for this bacterium to start growing show an inverse relationship. A lag time of 1-3 days was found as the content of acrylamide was raised from 100 to 1000 mg/L while growth was abolished at 1500 mg/L. The maximal growth rate increased as acrylamide concentrations increased, indicating an overall trend of increased toxicity.